Measuring assurance of learning (AOL) throught six-sigma process capability methodology - Taib, Che Azlan; Ahmad, Mohd Akhir (UUM College of Business, 2017)
UUM has earned AACSB (Association to Advance Collegiate Schools of Business) accreditation, the highest achievement for an educational institution that awards business degrees in 2016. AACSB mission is to advance quality management education worldwide through accreditation, through leadership and value-added services.According to this mission, having AACSB accreditation means UUM has to focus in the high quality academic program. This paper aims to explore and propose the application of six-sigma (6σ) process capability methodology in measuring course learning outcome (CLO).6σ is a highly disciplined process that helps the organization on developing and delivering valueadded products and services.This preliminary study also attempts to enhance the understanding and suggests the application of 6σ in measuring teaching-learning outcomes.In addition, it tries to predict the process variation, productivity and process capability of three assessment methods, namely quiz, assignment and the final examination.This study examines first-year undergraduate students for Quality Management System course at School of Technology Management and Logistics. A total of 50 students involve.